Design and Synthesis of CNS-targeted Flavones and Analogues with Neuroprotective Potential Against H2O2- and Aβ1-42-Induced Toxicity in SH-SY5Y Human Neuroblastoma Cells - Ana M. de Matos; Alice Martins; Teresa Man; David Evans; Magnus Walter; Maria Conceição Oliveira; Óscar López; José G. Fernandez-Bolaños; Philipp Dätwyler; Beat Ernst; M. Paula Macedo; Marialessandra Contino; et al. (MDPI AG, 2019)
With the lack of available drugs able to prevent the progression of Alzheimer’s disease (AD), the discovery of new neuroprotective treatments able to rescue neurons from cell injury is presently a matter of extreme importance and urgency. Here, we were inspired by the widely reported potential of natural flavonoids to build a library of novel flavones, chromen-4-ones and their C-glucosyl derivatives, and to explore their ability as neuroprotective agents with suitable pharmacokinetic profiles. All compounds were firstly evaluated in a parallel artificial membrane permeability assay (PAMPA) to assess their effective permeability across biological membranes, namely the blood-brain barrier (BBB). With this test, we aimed not only at assessing if our candidates would be well-distributed, but also at rationalizing the influence of the sugar moiety on the physicochemical properties. To complement our analysis, logD7.4 was determined. From all screened compounds, the p-morpholinyl flavones stood out for their ability to fully rescue SH-SY5Y human neuroblastoma cells against both H2O2- and Aβ1-42-induced cell death. Cholinesterase inhibition was also evaluated, and modest inhibitory activities were found. This work highlights the potential of C-glucosylflavones as neuroprotective agents, and presents the p-morpholinyl C-glucosylflavone 37, which did not show any cytotoxicity towards HepG2 and Caco-2 cells at 100 μM, as a new lead structure for further development against AD.